Developing Bread Business Strategy Using SWOT Analysis at Deira Bakery Store (Jurnal Manajemen Bisnis, 2024)
In recent years, the business landscape in Indonesia has experienced a significant increase through intense, dynamic, and unpredictable competition. To face increasingly fierce competition, it is necessary to implement the right business strategy. This study aims to determine and research using a qualitative descriptive approach. The object of this research is the Deira Bakery Gresik Store. Informants in this study are owners, employees, and consumers. The data collection technique in this research is in-depth interviews. Test the validity of the data using the source triangulation method by collecting data obtained through various sources. Data analysis intestine descriptive analysis methods and SWOT analysis to analyze the result of the data obtained using the IFAS and EFAS matrix. Based on the results of the analysis, a SWOT analysis diagram is produced, which shows that Toko Deira Bakery is in quadrant II position with a value of (X;Y) (1.38;-1.04), namely the ST strategy where the company situation uses internal strengths to overcome or respond to external threats. Therefore, the strategy that needs to be applied in this situation is to support the diversification strategy policy.